Land Use and Land Cover Change in Chure Conservation Area: A Study of Mithila Municipality, Dhanusha District, Nepal - Joshi, Krishna Dev; Poudel, Deepa Kumari (CV. Literasi Indonesia, 2024)
Chure Hills is considered as youngest Himalaya in the Himalayan chain. These hills are also considered vulnerable due to its fragile nature and unpredictable natural and human intervention. On this ground, this study attempts to explore the land use and land cover change pattern and its driving forces in the Chure-Terai hills of Mithila Municipality. This study involved the analysis of freely available satellite images of the study area which was downloaded from USGS. The Landsat 7 and Land sat 8 satellite images from 2000 to 2020 have been extracted for the land use/land cover mapping. Supervised classification has been carried out through Remote Sensing and GIS software. With reference of the Land Use Act, 2019 seven major classes have been classified in the study area which includes Forest area, Agriculture area, Settlement area, Grassland, Water body, Sediment Area, and Landslide Area. Based on observation throughout the research, despite the dominancy of forest and agriculture, both were declining continuously by -3.66% from 2000 to 2010 & -3.77% from 2010-2020 and agriculture area by -4.86% from 2000 to 2010 and -4.03% from 2010-2020. Similarly, increment of grassland or say barren land by (+7.26%) and (+4.02%) has been observed. This observation concluded that this change was due to human encroachment, and haphazard settlement. Side-by-side disaster events have also increased whereas the water body has been degrading due to the illegal extraction of construction materials from the Chure region and braided characteristics of the river.